Optimization of carbon and nitrogen sources for phytase production by Mitsuokella jalaludinii, a new rumen bacterial species - Lan, G.Q.; Abdullah, N.; Jalaludin, S.; Ho, Y.W. (Oxford University Press, 2002)
Aims: The effects of different carbon and nitrogen sources on phytase production by Mitsuokella jalaludinii were evaluated and the optimization of rice bran (RB) and soybean milk (SM) concentrations in the medium for phytase production was also determined.